2015
DOI: 10.1007/s00167-015-3850-y
|View full text |Cite
|
Sign up to set email alerts
|

Locking plate versus non-locking plate in open-wedge high tibial osteotomy: a meta-analysis

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 27 publications
0
21
0
1
Order By: Relevance
“…In contrast, several studies showed that OWHTO provided higher accuracy of correction than CWHTO [ 32 , 33 ]. There may be several reasons for the controversy about accuracy between the two HTOs, including differences in osteotomy technique, fixation device, and correction angle [ 11 , 34 36 ]. The present results showed that there was no significant difference in postoperative lower limb alignment between CWHTO and OWHTO, although there was a discrepancy in the preoperative planning with the same correction angle.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several studies showed that OWHTO provided higher accuracy of correction than CWHTO [ 32 , 33 ]. There may be several reasons for the controversy about accuracy between the two HTOs, including differences in osteotomy technique, fixation device, and correction angle [ 11 , 34 36 ]. The present results showed that there was no significant difference in postoperative lower limb alignment between CWHTO and OWHTO, although there was a discrepancy in the preoperative planning with the same correction angle.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving appropriate postoperative realignment is crucial . The rate of postoperative failure such as loss of correction decreased with the development of an internal fixation device . However, intraoperative correction errors still occur.…”
mentioning
confidence: 99%
“…5,6 The rate of postoperative failure such as loss of correction decreased with the development of an internal fixation device. [7][8][9] However, intraoperative correction errors still occur. One example is an increase in posterior tibial slope (PTS), which has various adverse effects on knee biomechanics.…”
mentioning
confidence: 99%
“…Predominant limitations of this approach include violation of the proximal tibiofibular joint and anterior extensor compartment, risk of peroneal nerve injury, loss of proximal tibial bone stock, and a more difficult conversion to total knee arthroplasty (TKA). 5,6 Medial opening wedge (MOW) HTO has demonstrated comparable efficacy in realigning the limb to unload the affected medial compartment, with lower complication rates. Correspondingly, it has become the procedure of choice for many surgeons.…”
mentioning
confidence: 99%
“…The advantages of this procedure over LCW osteotomy include avoiding the tibiofibular joint and peroneal nerve, maintaining proximal tibial bone stock, and easier conversion to TKA. 5,6 The biggest concern with the MOW HTO is the potential for loss of correction as well as the risk of nonunion. 7 Both of these issues demand rigid fixation to maintain the correction and allow appropriate healing.…”
mentioning
confidence: 99%